Exchange rate elasticity of exports and the role of institutions - Aygun Garayeva; Gulzar Tahirova (Graduate Institute of International and Development Studies, 2017)
The impact of institutional quality on the exchange rate-export relation is assessed in a panel of 33 countries and quarterly time period of 1991Q1- 2016Q3. Empirical estimation is conducted in 2 steps. As a first step, using panel DOLS, FMOLS and PMG estimation techniques, it is confirmed that a negative and significant relation between exchange rates and exports exists. The estimation suggests that in the countries under study, 1% appreciation of the real effective exchange rate leads to, approximately, 0.55% decrease in total exports on average, holding other variables constant. In a separate cross-sectional estimation using simple OLS, some empirical evidence has been found to prove that institutional quality positively affects the exchange rate elasticity of exports. Also it has been shown that in oil exporting countries institutional quality has a greater impact on exchange rate-export link, compared to oil importers. But these results are only weakly significant and are not robust to the use of other proxy variables.
Keywords: F14; F31; D73; C31; C33; 330; exchange rates; exports; institutional quality; oil exporters; panel data